2019
DOI: 10.1152/japplphysiol.01060.2018
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm shear modulus reflects transdiaphragmatic pressure during isovolumetric inspiratory efforts and ventilation against inspiratory loading

Abstract: The reference method for the assessment of diaphragm function relies on the measurement of transdiaphragmatic pressure (Pdi). Local muscle stiffness measured using ultrafast shear wave elastography (SWE) provides reliable estimates of muscle force in locomotor muscles. This study aimed at investigating whether SWE could be used as a surrogate of Pdi to evaluate diaphragm function. Fifteen healthy volunteers underwent a randomized stepwise inspiratory loading protocol of 0–60% of maximal isovolumetric inspirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 31 publications
(29 reference statements)
2
40
1
Order By: Relevance
“…We also paid extra attention to measure the shear modulus in muscles with no contractions and at the end of the expiration for the diaphragm. In the healthy controls, we report a diaphragm shear modulus above the range observed by Bachasson et al [23]. Two main differences should be noted between the two studies.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…We also paid extra attention to measure the shear modulus in muscles with no contractions and at the end of the expiration for the diaphragm. In the healthy controls, we report a diaphragm shear modulus above the range observed by Bachasson et al [23]. Two main differences should be noted between the two studies.…”
Section: Discussioncontrasting
confidence: 62%
“…SWE has been established as an excellent diagnostic method for liver fibrosis, breast cancer and thyroid cancer [21]. In skeletal muscles, it provides a spatial representation and quantifiable measurement of the mechanical properties and an approximate of the muscle fibrosis and the activity of the disease in chronic myopathy [22] as well as a surrogate of diaphragm force production in healthy volunteers during isovolumetric inspiratory efforts [23]. Although SWE muscle analysis may provide new data about muscle quality during critical illness, it has never been evaluated in the very specific critically ill population which is exposed to severe structural muscular alterations.…”
Section: Introductionmentioning
confidence: 99%
“…stiffness) measured using SWE has been shown to provide reliable estimates of passive and active muscle force in locomotor muscles [21,22]. Lately, we demonstrated that changes in diaphragm shear modulus (SMdi) reflect changes in Pdi during isovolumetric inspiratory efforts and ventilation against inspiratory loading in healthy subjects [23]. Recently, Flatres et al performed measurements of shear modulus in the diaphragm (i.e.…”
Section: Introductionmentioning
confidence: 80%
“…Moreover, shear wave elastography is considered to be more accurate and reproducible than evaluation of echogenicity, which is highly dependent on ultrasound settings (e.g., gain, contrast, etc.). A recently published proofof-concept work demonstrated that changes in diaphragm stiffness during inspiratory efforts as assessed with ultrasound shear wave elastography reflect changes in transdiaphragmatic pressure [74]. Therefore, it might offer a new non-invasive method for gauging diaphragm effort.…”
Section: Shear Wave Elastographymentioning
confidence: 99%